In vivo and in vitro antidiabetic studies of Pereskia bleo leaves - Ahmed, Qamar Uddin; Ahmad, Zulfadliza; Afrin, Mehnaz; Tunna, Tasnuva Sarwar; Ibrahim Apandi, Nur Amalina; Wan Zaini, Wan Norshakirah (2014)
Background review Since ancient times, plants have been used as natural agents to treat diseases particularly diabetes whose prevalence is increasing worldwide. Leaves of Pereskia bleo (Jarum Tujuh Bilah) are traditionally used to treat diabetes in many countries including Malaysia, however, no scientific claim exists in literature.